Analisis Sebaran Tingkat Kerentanan Erosi di Kawasan DAS Alo, Gorontalo - Arman, Anggriani; Rijal, Ahmad Syamsu; Dangkua, Talha; Jaya, Risman; Koto, Arthur Gani (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2024)
Alo Watershed Gorontalo Regency is one of the biggest contributors to watershed sedimentation in Limboto Lake, so it is necessary to conduct research on the distribution of erosion vulnerability levels in Alo Watershed. This study aims to determine the Analysis of the Distribution of Erosion Vulnerability Levels in the Alo Watershed Area, using the USLE (Universal Soil Loss Equation) method by finding the value of A, namely the amount of erosion that is influenced by rainfall (R), soil type (K), slope (LS). ), land use (C), and conservation measures (P) the calculation is the value of A = R x K x LS x C x P. The research results show that the total amount of erosion in the Alo Watershed area is 458,898.35  Ton/Ha/Year. Land use in the Alo watershed area is dominated by moorland or fields, therefore, to reduce the rate of erosion, land conservation measures are needed, for example changing land management habits by making bench terraces. Bench terraces can reduce the length of the slope and hold water so that it can reduce the speed of water flow on the surface.